2018
DOI: 10.1097/md.0000000000012225
|View full text |Cite
|
Sign up to set email alerts
|

ST segment elevation myocardial infarction (STEMI) patients are more likely to achieve lipid-lowering treatment goals

Abstract: Statin nonadherence or discontinuation is associated with increased cardiovascular events. Many factors related to the physicians or the patients are influential in this. We aimed to compare the compliance with statin therapy between the patients who first presented with ST-elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI), and unstable angina pectoris (UA) based on the target achievement according to the current dyslipidemia guidelines.We retrospectively acquired all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
5
1
Order By: Relevance
“…There was no noticeably difference between the two study results. Moreover, in recent studies whose population was STEMI patients in Turkey, the mean level of measured lipoprotein levels were similar with our measurement with a difference of ± 5% [5][6][7]. Additionally, our study had relatively small sample size, and the patients' demographic and laboratory findings could not be generalized to the whole population.…”
supporting
confidence: 77%
“…There was no noticeably difference between the two study results. Moreover, in recent studies whose population was STEMI patients in Turkey, the mean level of measured lipoprotein levels were similar with our measurement with a difference of ± 5% [5][6][7]. Additionally, our study had relatively small sample size, and the patients' demographic and laboratory findings could not be generalized to the whole population.…”
supporting
confidence: 77%
“…While the higher prevalence of acute coronary syndrome in men is also reflected in the current sample, replicating these findings in samples including a larger percentage of women would permit the examination of potential sex differences. In comparison with other studies [25], there was a high proportion of ST elevation in our sample. This may be explained by the fact that very few hospitals with equipment to perform coronary angiography exist in the area where the study was conducted, and therefore patients with ST elevation were referred to this teaching hospital at greater proportions than in other areas.…”
Section: Discussioncontrasting
confidence: 87%
“…For example, 57.3% of patients treated with high-potency statins in a study in Hong Kong ( n = 2850) did not achieve LDL-C goal 12 months post ACS compared with 63.4% of patients treated with non-high-potency statins [ 28 ]. Consistent findings were noted in a study of 1026 patients with ACS in Turkey, in which patients treated with high-intensity statin therapy were more likely to achieve LDL-C targets compared with patients prescribed lower doses of statins; however, LDL-C goal achievement was still low (≤ 45.2%) [ 29 ]. A further study of 2034 Chinese patients with ACS receiving LMT but not at LDL-C goal reported that 71.5% of these patients were receiving intensive statin therapy [ 30 ].…”
Section: Current State Of Dyslipidaemia Management Post Acs In Countrsupporting
confidence: 75%